Halogenotrinitromethanes: A Combined Study in the Crystalline and Gaseous Phase and Using Quantum Chemical Methods. Issue 40 (26th August 2014) - Klapötke, Thomas M.; Krumm, Burkhard; Moll, Richard; Rest, Sebastian F.; Vishnevskiy, Yury V.; Reuter, Christian; Stammler, Hans‐Georg; Mitzel, Norbert W.
Abstract The halogenotrinitromethanes FC(NO2)3 (1), BrC(NO2)3 (2), and IC(NO2)3 (3) were synthesized and fully characterized. The molecular structures of 1–3 were determined in the crystalline state by X‐ray diffraction, and gas‐phase structures of 1 and 2 were determined by electron diffraction. The HalC bond lengths in F, Cl, and BrC(NO2)3 in the crystalline state are similar to those in the gas phase. The obtained experimental data are interpreted in terms of Natural Bond Orbitals (NBO), Atoms in Molecules (AIM), and Interacting Quantum Atoms (IQA) theories. All halogenotrinitromethanes show various intra‐ and intermolecular non‐bonded interactions. Intramolecular N⋅⋅⋅O and Hal⋅⋅⋅O (Hal=F (1), Br (2), I (3)) interactions, both competitors in terms of the orientation of the nitro groups by rotation about the CN bonds, lead to a propeller‐type twisting of these groups favoring the mentioned interactions. The origin of the unusually short HalC bonds is discussed in detail. The results of this study are compared to the molecular structure of ClC(NO2)3 and the respective interactions therein.